Perbandingan Pemberian Buah Naga Dan Buah Bit Terhadap Kadar Hb Ibu Hamil Di PMB RY Kecamatan Panongan Kabupaten Tangerang: Comparison of Dragon Fruit and Beetroot Administration on Hb Levels of Pregnant Women at PMB RY, Panongan District, Tangerang Regency - Yanti, Rom Yul (Dohara POAJ, 2024)
Introduction: Anemia is a factor in maternal mortality. PMB RY Panongan District, Tangerang Regency, the target data for anemic pregnant women in 2020 is 13.6%; in 2021 it is 14.6% and in 2022 it is 15.8%. Prevention of anemia in pregnancy apart from Fe supplements can also be done by consuming foods that contain iron, such as dragon fruit and beets. Methods: Quasi-experimental design with pretest-posttest design with control group design. The sample is pregnant women who experience anemia in January-February 2023 as many as 30 samples using a purposive sampling technique. The intervention was given 250g once a day for 14 days. Bivariate analysis used paired sample t-test and independent t-test. Results: The results of a Univariate study of Hb levels of pregnant women before the administration of dragon fruit averaged = 10,247 gr/dl and after the administration of dragon fruit averaged = 10,627 gr/dl. Hb levels of pregnant women before the administration of beets averaged = 10,187 gr/dl and after the administration of beets averaged = 11,133 gr/dl. The results of the bivariate study obtained a p-value = 0,000. Discussion: There are differences in the effect of giving dragon fruit and beetroot on Hb levels of pregnant women. Pregnant women are expected to be diligent in consuming foods that contain iron, one of which is beetroot and lemon juice, and be obedient in consuming Fe tablets to increase Hb levels in the mother's blood.